2022
DOI: 10.14258/turczaninowia.25.1.9
|View full text |Cite
|
Sign up to set email alerts
|

New findings in the flora of Mongolia. Part 2

Abstract: New data on the distribution of 40 species from the families Asteraceae, Cystopteridaceae, Dryopteridaceae, Euphorbiaceae, Poaceae, Rosaceae, and Woodsiaceae in Mongolia are presented in the article. For the first time, Centaurea cyanus, Cystopteris almaatensis, Potentilla × habievii, Potentilla salsa, and Potentilla smirnovii are indicated for the flora of the country. 19 species previously known in the flora of Mongolia are new for its separate botanical and geographical regions. Of these, 7 taxa were found … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…This finding was published in one of the works of J. Soják, based on the collection of G. N. Ogureeva from the Ikh-Nuru ridge (Soják, 1994). Then, the species was found in other new locations: in the vicinity of the Duru-Nur Lake and the upper reaches of the Bodonchiin-Gol River (Ebel & Rudaya, 2002;Kechaykin et al, 2014); on the eastern macroslope of the Khadzhingin-Nuru ridge and on the Ulan-Daba pass at the headwaters of the Bulgan-Gol River (Kechaykin, 2015); in the vicinity of the Davst-Nur Lake (Kechaykin et al, 2022). These findings presents new localities of P. laevipes found by us on the eastern macroslope of the massif Munkh Khairkhan in the tracts of Nariin-Khag (ALTB: "catalogNumber" SHSHK 1223) and Ikh-Khag (ALTB: "catalogNumber" SHSHK 1259).…”
Section: Taxonomic History Morphology and Distributionmentioning
confidence: 99%
See 1 more Smart Citation
“…This finding was published in one of the works of J. Soják, based on the collection of G. N. Ogureeva from the Ikh-Nuru ridge (Soják, 1994). Then, the species was found in other new locations: in the vicinity of the Duru-Nur Lake and the upper reaches of the Bodonchiin-Gol River (Ebel & Rudaya, 2002;Kechaykin et al, 2014); on the eastern macroslope of the Khadzhingin-Nuru ridge and on the Ulan-Daba pass at the headwaters of the Bulgan-Gol River (Kechaykin, 2015); in the vicinity of the Davst-Nur Lake (Kechaykin et al, 2022). These findings presents new localities of P. laevipes found by us on the eastern macroslope of the massif Munkh Khairkhan in the tracts of Nariin-Khag (ALTB: "catalogNumber" SHSHK 1223) and Ikh-Khag (ALTB: "catalogNumber" SHSHK 1259).…”
Section: Taxonomic History Morphology and Distributionmentioning
confidence: 99%
“…The new annotated checklist of native vascular plants of Mongolia includes 76 Potentilla species (Baasanmunkh et al, 2022). In addition, three new species records of Potentilla were recently found in Mongolia (Kechaykin et al, 2022). Thus, of 79 representatives of the genus Potentilla, 13 are endemic to Mongolia (Baasanmunkh et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…A total of 3,041 native taxa belonging to 653 genera and 111 families have been recognized in Mongolia so far (Baasanmunkh et al, 2022a). In addition, six native taxa including Cystopteris almaatensis Kotukhov (Сystopteridaceae), C.A.Mey (Amaranthaceae; Sukhorukov et al, 2022b) and one alien species Centaurea cyanus L. (Asteraceae; Kechaykin et al, 2022) have recently been noted for western Mongolia. Of native taxa, 103 species are considered endemic to Mongolia (Baasanmunkh et al, 2021a(Baasanmunkh et al, , 2022a; however, some of them have been recently found in adjacent countries.…”
Section: Introductionmentioning
confidence: 99%